2021
DOI: 10.1002/lno.11758
|View full text |Cite
|
Sign up to set email alerts
|

Response of the seagrass Posidonia oceanica and its associated N2 fixers to high business‐as‐usual climate change scenario in winter

Abstract: We investigated the effects of increasing seawater temperature and CO2 concentration based on a high business‐as‐usual climate change scenario by year 2100 on the photosynthetic performance and productivity of Mediterranean seagrass Posidonia oceanica and alkaline phosphatase and N2‐fixing activities of microbes associated with different plant parts during winter when the plants may be thermally more vulnerable. Our results suggest that elevated CO2 and temperature benefit the overall photosynthetic performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Future experiments should explore the spatial extent of these metabolisms and test hypothesized interactions between the host, its microbiome, and carbon and nitrogen cycling. The importance of seaweeds and seagrasses to coastal productivity, and the demonstrated sensitivity of both the host and microbes to increasing temperatures and pH ( 14 , 38 , 52 ), pathogens ( 51 ), and other anthropogenic stressors, underline the importance of further studies of host-microbiome interactions in these foundational species.…”
Section: Discussionmentioning
confidence: 99%
“…Future experiments should explore the spatial extent of these metabolisms and test hypothesized interactions between the host, its microbiome, and carbon and nitrogen cycling. The importance of seaweeds and seagrasses to coastal productivity, and the demonstrated sensitivity of both the host and microbes to increasing temperatures and pH ( 14 , 38 , 52 ), pathogens ( 51 ), and other anthropogenic stressors, underline the importance of further studies of host-microbiome interactions in these foundational species.…”
Section: Discussionmentioning
confidence: 99%
“…However, significantly higher leaf net photosynthetic rates were still exhibited by plants subjected to 15.5 °C and high light treatment. On the other hand, in Agawin et al (2021), positive responses to higher temperature were observed in the photosynthetic activity of P. oceanica , while leaf respiration rates did not increase, suggesting that ocean warming scenarios may not necessarily have adverse effects on the carbon balance of the plants in winter. This agrees with the higher NPP rates estimated from the phyllosphere of P. oceanica at elevated temperature and high light conditions during the experiment.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, the APA values were on average the lowest under equal temperature and saturating light, regardless of the more favorable pH values for the phosphatases in this treatment, as they were higher compared to the low light treatments. This result could be attributed to the fact that at the final stage of the experiment the mean phosphate concentration for this treatment was several orders of magnitude higher than the rest (Table 1), given that APA in seagrasses decreases under elevated phosphate content and, vice versa, increases with phosphorus limitation (Invers et al, 1995;Martínez-Crego et al, 2006;Agawin et al, 2021). As for the significantly lower APA rates demonstrated by the rhizomes, this may suggest that the metabolic activity occurring in this part of the plants is relatively This is a provisional file, not the final typeset article low compared to the others, consequently, its inorganic phosphorus demand is low as well.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations